Keanekaragaman Jenis Amfibi di Kawasan Hutan Dengan Tujuan Khusus Oelsonbai, Kelurahan Fatukoa, Kecamatan Maulafa, Kota Kupang, Provinsi Nusa Tenggara Timur - Emanuel Edo; Maria M. E. Purnama; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was conducted to determine the Diversity of Amphibian Species in Forest Areas with Special Purpose Oelsonbai, Fatukoa Village, Maulafa District, Kupang City, East Nusa Tenggara Province. This research was carried out in October 2021. Data collection on the diversity of amphibian species used the VES (Visual Encounter Survey) method with transects and identification methods. Analysis of amphibian species diversity data using the formula for calculating the Shannon-Wienner diversity index (H') and species evenness (E). The results of this study found 5 types of amphibians from 4 families with a total of 158 individuals. family Bufonidae (1 species), family Dicroglossidae (2 species), family Rhacophoridae (1 species), and family Microhyladee (1 species). The diversity of amphibian species in KHDTK Oelsonbai line A (H'=1.27) while the diversity value in line B (H'=1.34). The diversity of the two paths is categorized as moderate. Physical characteristics such as air temperature, water temperature, and relative air humidity in KHDTK show values ​​that are suitable for amphibian life in general. Water temperature ranged from 26.5° to 30°C and air temperature ranged from 26° to 28°C while relative humidity ranged from 77% to 80% with a pH of 7.8 to 8.0.